Corpus Amazônida: a dança contemporânea no processo de identidade cultural da comunidade ribeirinha Bela Vista do lago do Puraquequara - Sicsú, Larissa da Silva (2022)
One of the most complex beginnings in the trajectory of the human being is the idea of identity, it becomes instigating to reflect on how it is expressed in the most physical character, which is the body. For the individual coming from unique spaces, such as the Amazon, the riverside stands out, especially the one around the city of Manaus, in particular that of the Bela Vista do Lago do Puraquequara community. In this sense, we sought to understand what this being is and how it manifests itself, its influences and movements fostered in its experience. In the light of a process guided by authors such as Pierre Bourdieu, Michel Foucault and Rudolf Laban, who approach, a priori, the body from different prisms, a dialectic that configures the individual as social praxis was highlighted. Emphasizing the body as a scenario and social influences, as an image of oneself and of the other in the disciplinary process and also as intentions and attributions of movements, listing elements from extensive studies relevant to the social sciences, highlighted from the theorists referenced in this. Guided by the art of Dance, especially the look at the body through the Liberating Dance, inspired by important names in contemporary dance, such as Klauss and Angel Vianna, this method based on bodily freedom, instigates the unveiling of organic dancing, of gestural expression. and emotions. Conducted by a qualitative bias, supported by a bibliographic survey and with the method of participant research, this work aimed to understand the identity nuances of the riverside populations. Thus, it was observed that through the field of theoretical dialogues and the experimentation carried out in the research field, primordial elements for this understanding were unveiled, highlighting the time-space relationship of this resident in line with the symbolic power of the waters; his self-affirmation as a riverside dweller, being a resident of the neighborhood or the lake, his decision to choose the community as a dwelling, as well as the expression of his poetics in his daily work. Thus, it was found that this resident incorporated his expressiveness in his relationship with nature and in community, an uninterrupted movement, like the seasonal waters of the Amazon. Despite the obstacles of the pandemic context, it was seen that the research objectives were achieved and that there is much to be understood about riverside populations, and continuity in the theme addressed is essential.